“Any Strange Beast There Makes a Man”: Interaction and Self-Reflection in the Arctic (1576-1578) - Sophie Lemercier-Goddard (Revue LISA)
The Arctic regions were the first contact zones in the New World where English explorers negotiated otherness and difference, before Francis Drake’s stay in California (July 1579) or the colonization attempt on Roanoke Island (1584-1587). Frobisher’s three voyages in search of the North-West Passage (1576-1578) brought together Englishmen and Inuit and set the pattern of a simple but barbarous people. The “country people” were conveniently characterized as “savages” – with the specter of cannibalism of which they were suspected backing up the model of the civilized Englishman, a paragon of virtue and civility. Interaction with the Inuit at home and abroad reveals exploration to be an exercise in self-definition, the colonial space emerging as an indispensible space of self-reflection (S. Gikandi, 1996). But there is also ample evidence of how frail such a construction is, and how confronted by Frobisher’s company, Inuit resisted the easy categorization and objectification.